Modern Climate Change Science:An Overview of Today’s Climate Change Science - Farmer, G. Thomas (Springer, 2015)
Composed of two extensive sections, this book surveys important work in climate change science, mainly in the United States, and introduces contributions to the body of science that have arrived on the scene between January 2013 and February 2014.